Alternative materials as an opportunity to reduce environmental impacts in the construction sector - Hernández-Zamora, María Fernanda (2021)
The constructions have become a serious environmental problem, because the high demand for natural resources and the massive production of large-scale waste that require special management. It’s necessary to rethink the materials used in the sector, and apply new technologies for extraction and production methods, as well as instruments that help in the reduction of the environment damages of constructions. In this way, was used a bibliographic search of various documents, mainly from the databases of the National University of Costa Rica, among other academic search engines. The methodological process was a qualitative investigation, where the theory and the literature review were the frame of reference. The objective was to identifying some of the alternative materials that can be replaced by the use of conventional materials, such as adobe, wood, hemp, straw, bamboo and eco-bricks made with household waste. The alternative materials are capable of giving the same structural support to a constructive work, in comparison with other conventional materials. This help to reduce the footprints of construction materials and improve the environmental materials that are low costs and other negative environmental impacts are minimized.